Bilateral striatal necrosis, dystonia and optic atrophy in two siblings. Issue 1 (January 1992) - Leuzzi, V; Bertini, E; De Negri, A M; Gallucci, M; Garavaglia, B
Abstract : Two siblings developed a neurological disorder in the first decade characterised by generalised dystonia, hypokinesia, and subacute visual loss. CT and serial MRI examinations showed bilateral lesions of the striatum, mainly in the putamen. The classification of these patients is discussed in relation to infantile bilateral striatal necrosis (IBSN), Leigh's disease, and Leber's optic neuropathy. The literature shows a clinical and aetiopathogenetic overlap between these syndromes. In our cases parental consanguinity and the involvement of a single generation suggest a new clinical condition with autosomal recessive transmission.